New species of Elaphidiini (Coleoptera, Cerambycidae) from Bolivia - Galileo, Maria Helena M.; Martins, Ubirajara R.; Santos-Silva, Antonio (Zootaxa, 2014)
Five new Elaphidiini species are described from Bolivia including Anelaphus maculatus sp. nov. from Tarija and Mephritus bonasoi sp. nov., M. meyeri, sp. nov., M. punctulatus sp. nov. and M. eleandroi sp. nov. from Santa Cruz. A revised key to all 22 South American Mephritus species is provided.